Social Support and Self Efficacy Predict Adolescent Well Being: Dukungan Sosial dan Efikasi Diri Memprediksi Kesejahteraan Remaja - Auliyah Rohmah; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Subjective well-being constitutes a multidimensional construct encompassing positive affect, minimal negative affect, and cognitive evaluations of life satisfaction, representing a central indicator of adolescent psychological functioning. Specific Background: Adolescents living in orphanages encounter distinct developmental challenges due to limited parental care, making social support and self-efficacy salient psychosocial resources within institutional settings. Knowledge Gap: Although prior studies have examined social support or self-efficacy separately, limited empirical evidence addresses their simultaneous association with subjective well-being among adolescents residing in orphanages. Aims: This study aimed to examine the relationships between social support and self-efficacy with subjective well-being among adolescents living in orphanages in the Candi region. Results: Using a quantitative correlational design with saturated sampling of 106 adolescents, data were analyzed through multiple correlation analysis. Findings revealed significant positive correlations between social support and subjective well-being (r = 0.407, p < .001) and between self-efficacy and subjective well-being (r = 0.489, p < .001). Simultaneously, both predictors were significantly associated with subjective well-being (F = 25.300, p < .001), accounting for 32.9% of the variance (R² = 0.329). Most participants were categorized at moderate levels across variables. Novelty: This study integrates social support and self-efficacy within a single predictive model focused specifically on adolescents in orphanage contexts. Implications: Strengthening perceived social support and self-efficacy may serve as strategic targets for psychosocial programs aimed at promoting adolescent subjective well-being in institutional care environments. Highlights: Perceived Interpersonal Assistance Showed a Statistically Significant Positive Correlation With Life Satisfaction and Affective Evaluation. Personal Capability Beliefs Demonstrated a Stronger Correlation Coefficient Compared With External Relational Resources. The Combined Model Explained 32.9% of Variance Among Youths Residing in Institutional Care Settings Keywords: Subjective Well-Being, Social Support, Self-Efficacy, Adolescents, Orphanages